The effect of incorporation of red lentils flour on the quality of non-fried instant noodle / Ili Fatimah Ismail - Ismail, Ili Fatimah (Faculty of Applied Sciences, 2008)
The aim of this study was to develop non-fried instant noodles in which lentils flour was added at 10, 30 and 50 percent levels. The products were compared to a control noodle (100% wheat flour). It was observed that the protein, ash and moisture content increased significantly (p<0.05) when the level of lentils flour was increased. There was no significant difference (p<0.05) between all samples for fat and crude fiber content. The lightness (‘L’ value) and yellowness (‘b value) decreased significantly (p<0.05) when the level of lentils flour was increased. In the other hand, the redness (‘a’ value) was increased significantly (p<0.05) when the level of lentils flour was increased. The firmness increased significantly (p<0.05) with lentils flour level and was evidenced by both instrumental analysis and quantitative descriptive analysis (QDA). The QDA showed that the perception in overall appearance, elasticity, smoothness, overall texture and overall quality increasingly deviate from the control with increased addition of lentils flour. However, yellowness, firmness and after taste were increased with increasing lentils flour into non-fried instant noodle. The incorporation of red lentil flour noodles with 10% lentils flour level was considered to be as acceptable as the control for overall quality and taste on hedonic scale rating given by panelists.